Phage detection in the rhizosphere of higher antarctic plants using transmission electron microscopy - Mas, O.; Andriychyk, O.; Polischuk, V. (Ukrainian Antarctic Journal, 2013)
This work is focused on electron microscopy of soil samples from root zone of higher Antarctica plants Deschampsia antarctica and Colobanthus quitensis for detection of bacteriophages. Here we compared several techniques and proposed optimal method for isolation of phage suspensions from the substrate. For the first time, the biodiversity of bacteriophages and virus-like particles (VLPs) in the root zone of Antarctic plants has been evaluated. According to morphological description, the dimensions and taxonomic position of several bacteriophages were elucidated. Possible reasons for degradation of virus particles observed during the microscopy studies have been suggested.